2013
DOI: 10.1002/jlcr.3170
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new fluorine‐18 glycosylated ‘click’ cyanoquinoline for the imaging of epidermal growth factor receptor

Abstract: This study reports the radiosynthesis of a new fluorine-18 glycosylated 'click' cyanoquinoline [(18) F]5 for positron emission tomography imaging of epidermal growth factor receptor (EGFR). The tracer was obtained in 47.7 ± 7.5% (n = 3) decay-corrected radiochemical yield from 2-[(18) F]fluoro-2-deoxy-β-d-glucopyranosyl azide, and the overall nondecay-corrected radiochemical yield from aqueous fluoride was 8.6 ± 2.3% (n = 3). An in vitro preliminary cellular uptake study showed selectivity of the tracer for EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The high lipophilicity (Log P ) of FED6 (3.85) (Fig 1) is thought to contribute at least in part to this property. We recently reported the synthesis of a glycosylated cyanoquinoline derivative, FED20, designed to reduce the lipophilicity [31]. The Log P of FED20 was significantly lower than that of FED6 at 2.51, while retaining affinity for EGFR; IC50 for inhibition of cell-free EGFR phosphorylation was 4.5 nM compared to 1.8 nM for FED6 [18,31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high lipophilicity (Log P ) of FED6 (3.85) (Fig 1) is thought to contribute at least in part to this property. We recently reported the synthesis of a glycosylated cyanoquinoline derivative, FED20, designed to reduce the lipophilicity [31]. The Log P of FED20 was significantly lower than that of FED6 at 2.51, while retaining affinity for EGFR; IC50 for inhibition of cell-free EGFR phosphorylation was 4.5 nM compared to 1.8 nM for FED6 [18,31].…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported the synthesis of a glycosylated cyanoquinoline derivative, FED20, designed to reduce the lipophilicity [31]. The Log P of FED20 was significantly lower than that of FED6 at 2.51, while retaining affinity for EGFR; IC50 for inhibition of cell-free EGFR phosphorylation was 4.5 nM compared to 1.8 nM for FED6 [18,31]. While features such as MW, PSA, and n(N+O) were still suggested of active efflux, we predicted that FED20 would have improved uptake selectivity profile due to the lower Log P [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18 F-glycosylation via CuAAC was also transferred to the radiosyntheses of a couple of nonpeptidic compounds [2329]. For the radiosynthesis of an 18 F-fluoroglycosylated folate derivative by Fischer et al, the intermediate 3,4,6-tri- O -acetyl-2-deoxy-2-[ 18 F]fluoroglucopyranosyl azide 2 was separated by solid phase extraction, excluding the HPLC purification [23].…”
Section: 18f-fluoroglycosylation Via Copper-catalyzed Azide-alkynementioning
confidence: 99%
“…In a study reported by Pisaneschi et al 2-deoxy-2-[ 18 F]fluoroglucopyranosyl azide 3 was used for the radiosynthesis of a new 18 F-fluoroglycosylated cyanoquinoline for PET imaging of epidermal growth factor receptor (EGFR) [29]. In this study 3 was not isolated by HPLC, but only separated via SPE.…”
Section: 18f-fluoroglycosylation Via Copper-catalyzed Azide-alkynementioning
confidence: 99%